Off-Axis Diffractive Optics for Compact Terahertz Detection Setup - Paweł Komorowski (Applied Sciences, 2020)
Medical and many other applications require small-volume setups enabling terahertz imaging. Therefore, we aim to develop a device for the in-reflection examination of the samples. Thus, in this article, we focus on the diffractive elements for efficient redirection and focusing of the THz radiation. A terahertz diffractive optical structure has been designed, optimized, manufactured (using extrusion-based 3D printing) and tested. Two manufacturing methods have been used—direct printing of the structures from PA12, and casting of the paraffin structures out of 3D-printed molds. Also, the limitations of the off-axis focusing have been discussed. To increase the efficiency, an iterative algorithm has been proposed that optimizes off-axis structures to focus the radiation into small focal spots located far from the optical axis, at an angle of more than 30 degrees. Moreover, the application of higher-order kinoform structure design allowed the maintaining of the smallest details of the manufactured optical element, using 3D printing techniques.